2015
DOI: 10.1038/ncomms7641
|View full text |Cite
|
Sign up to set email alerts
|

Skp2–MacroH2A1–CDK8 axis orchestrates G2/M transition and tumorigenesis

Abstract: Understanding the mechanism by which cell growth, migration, polyploidy, and tumourigenesis are regulated may provide important therapeutic strategies for cancer therapy. Here we identify the Skp2-macroH2A1 (mH2A1)-CDK8 axis as a critical pathway for these processes, and deregulation of this pathway is associated with human breast cancer progression and patient survival outcome. We showed that mH2A1 is a new substrate of Skp2 SCF complex whose degradation by Skp2 promotes CDK8 gene and protein expression. Stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
86
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 37 publications
4
86
1
Order By: Relevance
“…Indeed, Xu et al . [22] very recently reported that CDK8 is implicated in breast carcinogenesis and that the expression of CDK8 protein (or, more precisely, CDK8/19, since these authors used the same cross-reactive antibody as in our study) is positively correlated with tumor status, nodal metastasis and stage in breast cancer. CDK8 gene expression was found to be elevated by Skp2 SCF complex that promotes the ubiquitination and degradation of histone variant macroH2A, a negative regulator of CDK8 expression [15].…”
Section: Immunohistochemical Analysis Of Cdk8/19 Protein Expression Imentioning
confidence: 60%
See 1 more Smart Citation
“…Indeed, Xu et al . [22] very recently reported that CDK8 is implicated in breast carcinogenesis and that the expression of CDK8 protein (or, more precisely, CDK8/19, since these authors used the same cross-reactive antibody as in our study) is positively correlated with tumor status, nodal metastasis and stage in breast cancer. CDK8 gene expression was found to be elevated by Skp2 SCF complex that promotes the ubiquitination and degradation of histone variant macroH2A, a negative regulator of CDK8 expression [15].…”
Section: Immunohistochemical Analysis Of Cdk8/19 Protein Expression Imentioning
confidence: 60%
“…CDK8 gene expression was found to be elevated by Skp2 SCF complex that promotes the ubiquitination and degradation of histone variant macroH2A, a negative regulator of CDK8 expression [15]. The oncogenic role of CDK8 in breast cancer was suggested to be due to CDK8 facilitating the degradation of cell cycle inhibitor p27 [22]. …”
Section: Immunohistochemical Analysis Of Cdk8/19 Protein Expression Imentioning
confidence: 99%
“…Various studies have discovered that Skp2 plays an important role in tumorigenesis in a variety of human types of cancer (40,41). However, the function of Skp2 in OS remains largely obscure.…”
Section: Discussionmentioning
confidence: 99%
“…CDK8/19 regulation is especially pertinent in cancers, where CDK8 positively regulates several cancer-relevant signaling pathways (5), including Wnt/β-catenin (9), the serum response network (6), TGFβ (10), HIF1α (7), and estrogen receptor (8). CDK8 has been identified as an oncogene implicated in colorectal (9), pancreatic (11), and breast (3,8,12,13) cancers and melanomas (14) and associated with the stem cell phenotype (15). CDK8/19 inhibition also has an antiproliferative effect in a subset of leukemias (16,17).…”
Section: Significancementioning
confidence: 99%